1997
DOI: 10.1007/s004680050111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon dioxide, fertilization and irrigation on loblolly pine branch morphology

Abstract: AbstractmFoliage and wood parameters of branches of 12-year-old loblolly pine (Pinus taeda L.) trees were characterized after 21 months of exposure to fertilizer, irrigation and elevated CO2 treatments. Branches of loblolly pine trees were enclosed in plastic chambers and exposed to ambient, ambient +175 and ambient +350 umol mol -1 CO2 concentrations. Measurements of foliage and wood at the fascicle, flush and branch levels were made at the end of the 21 month study period. The +350 CO2 treatment did not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
(50 reference statements)
2
26
2
Order By: Relevance
“…Two previous studies in loblolly pine found that high nutrient availability was associated with longer and thicker fascicles (Shelton and Switzer 1984;Murthy and Dougherty 1997). In one study, however, fertilization decreased SNA (Murthy and Dougherty 1997) and in the other, good site quality was associated with increased SNA (Shelton and Switzer 1984).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Two previous studies in loblolly pine found that high nutrient availability was associated with longer and thicker fascicles (Shelton and Switzer 1984;Murthy and Dougherty 1997). In one study, however, fertilization decreased SNA (Murthy and Dougherty 1997) and in the other, good site quality was associated with increased SNA (Shelton and Switzer 1984).…”
Section: Introductionmentioning
confidence: 84%
“…In general, greater nutrient availability increases foliage dimensions of Pinus (Shelton and Switzer 1984;Conroy et al 1986;Gholz 1986;Raison et al 1992;Murthy and Dougherty 1997;Niinemets et al 2001). The extent that leaf dimensions are plastic in response to nutrient supply may have important implications regarding the ability of canopies to adjust their capacity to capture light and photosynthesize.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…There is evidence that, in conifers, branchiness may increase with decreasing site water availability [5]. In addition, increases in soil nutrient availability generally lead to enhanced branch extension growth [47,67], as well as higher fractional biomass investment in foliage [59], and greater total plant foliar area [47,70,73]. The branching responses to nutrient availability have not been investigated extensively in trees, and it is not clear whether the nutrientrelated increase in branch extension is sufficient to support the extra foliar area, or whether the improved nutrition also leads to greater shoot production and more frequent branching.…”
Section: Introductionmentioning
confidence: 99%
“…However, Pinus taeda did not respond to elevated CO 2 unambiguously. SWD of this species was increased (Doyle 1987) or decreased (Oren et al 2001) and also remained stable (Murthy, Dougherty 1997;Telewski et al 1999;Roderick 2001). These inconsistent results obtained for individual coniferous species can be also caused by differences in cultivation design and also in fumigation duration.…”
mentioning
confidence: 90%